Conscious Energy Consumption: Conscious Energy Consumption (Health and Biosciences, 2025)
The objective of this study was to identify high school students' perceptions, through inquiry-based learning, about electricity consumption and its relationship with the environment, as well as to promote awareness of the importance of conscious use for society as a whole, involving economic issues and sustainability. Initially, knowledge was constructed through a cooperative learning approach on the concepts of  energy, its forms of production, and impacts on the environment, which was important to connect them to the topic. Based on their prior knowledge, students thought and discussed the importance of conscious consumption for the environment, reflected on their behavior regarding energy consumption, and related the appliances that, in their view, are the main responsible for the highest energy consumption in their residence. Most students believed that lamps and refrigerators were the main appliances related to energy consumption. After data collection, the information was analyzed, and students were able to compare it to the hypotheses previously developed. The results obtained highlight that, although the construction of knowledge about the types of energy and their impact on the environment has had a considerable effectiveness, it is important to think about the use of methodologies that are capable of building a more solid knowledge about the concept and consumption of electricity, as well as promoting understanding of the distinction between the use of water and the use of energy, since at various times the two situations were considered the same problem.
Keywords: high school; energy consumption; investigation-based teaching